Effects of Ambient Noise Isolation on Illness Severity and Mental Health Among Hospitalized Children with Asthma: Retrospective Study - Xiaoqing Li; Yunfang Li; Wenwen Guo; Yanling Zhang (Noise and Health)
Objective: This study investigated the effects of ambient noise isolation on disease severity and mental health among hospitalized children with asthma. Methods: A retrospective analysis was conducted on the clinical data of 187 hospitalized children with asthma admitted from May 2021 to May 2023. Among them, 92 cases were categorized in the control group (conventional management) and 95 in the observation group (environmental noise isolation). Ambient noise level, disease severity, mental health, and sleep quality were observed and compared between the two groups. Results: Weekly time, the noise value of the observation group was lower than that of the control group (P < 0.05). Before the management, modified Tal scoring system, cough symptom score, and Spence Children’s Anxiety Scale-Short Version (SCAS-S) were recorded. SCAS-S and Sleep Disturbance Scale for Children (SDSC) had no significant difference (P > 0.05). Weekly time, no differences in the score of social fear dimension of SCAS-S, score of excessive sweating dimension of SDSC, Tal score, and cough symptom score were found between the observation and control groups (P > 0.05). The scores of other dimensions of SCAS-S and SDSC were lower in the observation group than those in the control group (P < 0.05). Conclusions: Environmental noise isolation for hospitalized children with asthma can effectively improve their mental health and sleep status, but this strategy cannot improve their disease.